Revealing intrinsic spin coupling in transition metal-doped graphene - Zhou, Han; Hu, Xiuli; Fang, Wei-Hai; Su, Neil Qiang (Physical chemistry chemical physics : PCCP, 2022)
Graphene materials offer attractive possibilities in spintronics due to their unique atomic and electronic structures, which is in contrast to their limited applications in the design of sophisticated spintronic devices. This should be attributed to the lack of knowledge about the intrinsic characteristics of graphene materials, especially the diverse correlations between sites within the materials and their roles in spin-signal generation and propagation. This work comprehensively studies the spin couplings between transition metal atoms doped on graphene and reveals their potential application in spintronic device design through the realization of various logic gates. In addition, the effects of the distance between doped metal atoms and the number of carbon layers on the logic gate implementation further verify that the spin-coupling effect can exhibit a certain distance dependence and space propagation. The achievements in this work uncover the potential value of graphene materials and are expected to open up new avenues for exploring their application in the design of sophisticated spintronic devices. Diverse spin couplings create attractive possibilities for novel applications of graphene materials.